Challenges of digitizing manuscripts at the University of Algeria - sebaihi, billel (El Omda in Linguistics and Discourse Analysis, 2025)
above, I have prepared an article entitled: Manuscripts and the challenges of digitization in Algerian Universities. It is a question of answering questions related to this reality, which requires careful examination to ensure the effectiveness of the manuscripts, taking into account the development of technologies.